Sino-African relation : from a view of international political economy - Li, Li (2008)
In this paper I argue that it is reasonable for China and Africa to enjoy a sound relation with each other due to historical political and economic reasons. First, China and Africa have had a long history of exchange and similar suffering from colonization, which is the precondition or their relation at present. Second, China and Africa could give each other political support both at domestic and international level, which becomes a key reason for a close Sino-African tie. And third, economic cooperation between China and Africa are in line with the interest of both sides, largely due to the complementary economic structure of them.